2018
DOI: 10.31234/osf.io/fgrnx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evolutionary perspective on paranoia

Abstract: Although paranoia is the most commonly presenting symptom of psychosis, paranoid thoughts occur frequently in the general population and range widely in severity, from mild socio-evaluative concerns to frank delusions about the harmful intentions of others. Furthermore, paranoia commonly appears after a surprisingly diverse range of difficulties including trauma, brain injury, sleep deprivation, drug use, and psychiatric and neurological disorder. Evolutionary accounts of paranoia have been proposed before but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 101 publications
(117 reference statements)
1
18
1
Order By: Relevance
“…Importantly, our findings were not attributable to subjective mood, beliefs in general, nor scepticism about whether participants were playing real partners. These findings are consistent with imaging and physiological evidence (Baez-Mendoza et al, 2013), and evolutionary accounts (Raihani & Bell, 2019), that identify a key role for dopamine in social inference. Future research should aim to use live, social process-oriented tasks in combination with imaging and pharmacology to better understand the role of dopamine in social attributions and its interaction with psychosocial factors (such as social stress) which are known to increase risk for psychosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, our findings were not attributable to subjective mood, beliefs in general, nor scepticism about whether participants were playing real partners. These findings are consistent with imaging and physiological evidence (Baez-Mendoza et al, 2013), and evolutionary accounts (Raihani & Bell, 2019), that identify a key role for dopamine in social inference. Future research should aim to use live, social process-oriented tasks in combination with imaging and pharmacology to better understand the role of dopamine in social attributions and its interaction with psychosocial factors (such as social stress) which are known to increase risk for psychosis.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, it has been previously suggested that the integration of information in the striatum is critical for social interactions and relationships (Baez-Mendoza & Schultz, 2013). Specifically, we suggest that dopamine may modulate the representation of threat during social interactions, as social threat is an evolutionarily important focus of attention (Raihani & Bell, 2019). Evidence from mice, for example, suggests a specific subcortical dopaminergic circuit for environmental threat detection and avoidance (Menegas et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…Although paranoia traditionally referred to delusional paranoia, a broader spectrum of paranoid concerns also occurs in a range of psychiatric syndromes and throughout the general population where it can encompass perceptions of social reference and hostility, suspicious thoughts and mistrust of others, and fears of persecution ( Bebbington et al, 2013 ; Combs et al, 2006 ; Elahi et al, 2017 ; Freeman, 2016 ; Green et al, 2008 ). Paranoia shows full taxometric continuity across clinical and nonclinical populations ( Ahmed et al, 2012 ; Edens et al, 2009 ; Elahi et al, 2017 ), supporting a dimensional approach to paranoia and suggesting that studying the cognitive and affective correlates of paranoid thinking in the general population will yield insights into more severe paranoia in clinical settings ( Freeman et al, 2005 ; Raihani & Bell, 2019 ). Our aim is to determine whether paranoia correlates with altered social reward value, and whether this predicts social behavior in an experimental setting.…”
mentioning
confidence: 81%
“…Perhaps using a spiritual, moral or social justice base, or more simply from an understanding of what is possible in education, they have the courage to what is right to help their students be the best they can. Chapters from the fourth book illustrate this courage well [21,[35][36][37][38][39].…”
Section: Personal Resourcesmentioning
confidence: 99%
“…These models have been developed by two Australian groups, from doctoral research supervised by the Australian researchers in Singapore and Indonesia, and from the Cyprus research group full accounts of these models can be found in [11,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Across most of these models from the four countries, establishing collective direction, developing people and improving teaching and learning are common and explicit, and implicitly there is a sense of being able to lead change.…”
Section: A Model Of How Successful School Leadership Influences Studementioning
confidence: 99%